2021
DOI: 10.1016/j.xkme.2020.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal Dialysis Modality Failure in a Middle-Income Country: A Retrospective Cohort Study

Abstract: Technique failure in peritoneal dialysis (PD) remains one of the most critical challenges of this therapy and is associated with a significant increase in costs and morbidity. Our objective was to estimate the frequency of PD technique failure and identify factors associated with technique failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…Other studies have found other factors linked with an increased risk of PD discontinuation, such as peritonitis and male sex [24]. In addition, the outcome disparity between the two sexes has been observed in some studies but has not been explained.…”
Section: Discussionmentioning
confidence: 94%
“…Other studies have found other factors linked with an increased risk of PD discontinuation, such as peritonitis and male sex [24]. In addition, the outcome disparity between the two sexes has been observed in some studies but has not been explained.…”
Section: Discussionmentioning
confidence: 94%
“…Other studies have found other factors linked with an increased risk of PD discontinuation, such as old age, diabetes, peritonitis, and male sex [ 25 , 26 ]. The outcome disparity between the two sexes has been observed in some studies but has not been explained.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that peritonitis is one of the most important causes for technique failure with PD [ 41 , 42 ]. Despite the heightened risk of peritonitis, death-censored technique survival was not found to be significantly different between elderly and non-elderly patients in our meta-analysis.…”
Section: Discussionmentioning
confidence: 99%